Heavy Metals Contamination in Water, Soil and Plant Samples of Okomu National Park, Edo State, Nigeria (African Journal of Biomedical Research, 2020)
The pollution of the environment with a wide range of contaminants has become a matter of great concern over the last few decades. Heavy metals are considered to be one of the main contaminants in the environment, since they have a significant effect on ecological quality. They have the capability to move from contaminated soils and water and bioaccumulate in plant species that herbivores ingest causing health risks to various organisms in the food chain as a result of bioaccumulation. This study therefore assessed the levels of heavy metals in water, soil and plant samples of Okomu National Park, Edo State, Nigeria. Water samples were collected by grab sampling while top soil (0-15 cm) and plant samples were collected randomly. Samples of water (8), soil (8) and plant (6) were collected for two seasons (dry and wet) and analysed for heavy metals: Copper (Cu), Nickel (Ni), Chromium (Cr), Zinc (Zn), Iron (Fe), Lead (Pb), Manganese (Mn) and Cadmium (Cd) using Atomic Absorption Spectrophotometer after wet (acid) digestion. Data collected were subjected to descriptive (mean, standard deviation) and inferential (T-test) statistics using Statistical Package for Social Sciences with statistical significance set at α0.05. The mean values of heavy metals in the water samples revealed that all the heavy metals analysed (except Cu and Zn) were above the WHO guidelines for drinking water. The level of Cd in the soil samples was higher than the comparable maximum allowable limit while the mean values of all the analysed heavy metals (except Zn) in the sampled plant species were above the comparable WHO permissible limit. Significant seasonal variation in the concentration of heavy metals was observed in the study as there was more metal contamination in all the analysed samples during the wet season. The concentrations of analysed heavy metals and influence of seasonal variation observed in this study may have negative implication on wildlife health within Okomu National Park. As such, there is need to carry out the study (in sediments inclusive) over time so as to monitor heavy metal deposition and route of exposure in the park.